Milton's Angels : the Early-Modern Imagination. - Raymond, Joad (OUP Oxford, 2010)
Milton's Paradise Lost, the most eloquent, most intellectually daring, most learned, and most sublime poem in the English language, is a poem about angels. It is told by and of angels; it relies upon their conflicts, communications, and miscommunications. They are the creatures of Milton's narrative, through which he sets the Fall of humankind against a cosmic background. Milton's angels are real beings, and the stories he tells about them rely on his understanding of what they were and how they acted. While he was unique in the sublimity of his imaginative rendering of angels, he was not alone.